Eight-season epidemiological study of injuries in men`s international Under-20 rugby tournaments - Fuller, C. W.; Taylor, A.; Raftery, M. (Journal of Sports Sciences, 2018)
The aim of this study was to define the incidence and nature of match injuries sustained in men`s international under-20 rugby. The study comprised an 8-season prospective study of 16 international under-20 rugby tournaments. Procedures complied with the consensus statement for epidemiological studies in rugby. Outputs included players` mean age, stature and body mass and incidence, severity, location, type and cause of match injuries. The overall incidence of injury was 49.7 injuries/1000 player-match-hours (backs: 48.3; forwards: 50.9) with a mean severity of 32.2 days-absence (backs: 29.4; forwards: 34.4). There were no significant changes in incidence or severity of injury over the study period. Shoulder/clavicle (18.3%), head/face (16.4%), knee (13.7%) and ankle (13.7%) were the most common injury locations and ligament sprain (35.4%), haematoma/bruise (15.9%), concussion (12.5%) and muscle strain (11.2%) the most common types of injury. Being-tackled (29.2%), tackling (24.0%) and collisions (14.3%) were the most common events leading to injury. The results confirm that international under-20 rugby has a high incidence and severity of injury but the incidence is half that reported for senior international players. There was no significant change in the overall incidence of injury at the Under-20 level in the period 2008 to 2016.